2010
DOI: 10.1002/ptr.3172
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of aqueous extract of Chicorium intybus L. leaves on offspring sex ratio in rat

Abstract: A traditional belief in Iranian culture indicates that parental consumption of chicory leaves (Chicorium intybus L.) affects the gender of newborns. The aim of this study was to investigate the effect of aqueous extract of chicory on offspring sex ratio in rat. All rats in experimental groups 1 and 2 were i.p. injected with either 1.0 or 0.7 g/kg body weight (LD50 = 2.244 g/kg) of an aqueous extract of chicory leaves for 30 days at 72 h intervals. The control rats were injected with distilled water in the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Cichorium intybus is well known in the folk and modern medicine for its anticancer [ 13 ], antioxidant [ 14 ], antidiabetic [ 15 ], anti-inflammatory [ 16 ], antimicrobial [ 17 ], anthelmintic [ 18 ], analgesic [ 19 ], cardiovascular [ 20 ], gastroprotective [ 21 ], hepatoprotective [ 22 ], immunological [ 23 ], reproductive effects [ 24 ], wound healing abilities [ 25 ], and many other pharmacological applications [ 17 , 26 ]. It is also important to mention the numerous active substances of this species: alkaloids, coumarins, caffeic acid derivatives, sesquiterpene lactones, flavonoids, terpenoids, and volatile compounds [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cichorium intybus is well known in the folk and modern medicine for its anticancer [ 13 ], antioxidant [ 14 ], antidiabetic [ 15 ], anti-inflammatory [ 16 ], antimicrobial [ 17 ], anthelmintic [ 18 ], analgesic [ 19 ], cardiovascular [ 20 ], gastroprotective [ 21 ], hepatoprotective [ 22 ], immunological [ 23 ], reproductive effects [ 24 ], wound healing abilities [ 25 ], and many other pharmacological applications [ 17 , 26 ]. It is also important to mention the numerous active substances of this species: alkaloids, coumarins, caffeic acid derivatives, sesquiterpene lactones, flavonoids, terpenoids, and volatile compounds [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an experiment on sows to check whether the mineral imbalance in the diet of the female before fertilization affects the sex ratio of the progeny, out of a total of 677 births, the sex ratio was 55.7 with the sodium and potassium diet and 48.3 with the calcium and magnesium diet [14]. Celik et al [5] and Behnam-Rassouli et al [6] reported that ration consisting of high levels of sodium and potassium caused the number of male sex to increase in each gestation, although this finding is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…There are also methods which use different food combinations and special diets to maximize the chance of having a fetus with specific sex. Some believe that the ratio of the mineral's sodium, potassium, calcium and magnesium are important in determination of fetus gender [5,6].It is reported that both Mg absorption and retention increased when steers were fed Monensin [7]. Also, high levels of sodium in the sodium selenite may increase the level of blood sodium, potassium and several metabolites and elements in the blood [8].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Imam Reza eighth Shiite (Shia) leader has said: "eating of sweet pomegranates enhances the men's sexual force leads to the beauty of the child" [15]. The recent researches show that Pomegranate consumption improves the quality of sperm (number, motility, percentage, and natural morphology of the sperm) [16,17]. Templeton (1995) reported that prescribing a suitable amount of pomegranate extract improved the quality of sperm [18].…”
Section: Pomegranatementioning
confidence: 99%